Continuous flow reactions in water for the synthesis of propargylamines via a metal-free decarboxylative coupling reaction. Issue 32 (5th August 2015) - Jung, Bongkyun; Park, Kyungho; Song, Kwang Ho; Lee, Sunwoo
Graphical abstract: A range of propargylamines was synthesized via the metal-free decarboxylative coupling of alkynyl carboxylic acids with amines and paraformaldehyde in water, using a continuous flow reaction system. Aryl- and alkyl-substituted propiolic acids were found to react with secondary amines in the presence of paraformaldehyde, at 140 °C in water to give the desired propargylamines in good yield. Abstract: A range of propargylamines was synthesized via the metal-free decarboxylative coupling of alkynyl carboxylic acids with amines and paraformaldehyde in water, using a continuous flow reaction system. Aryl- and alkyl-substituted propiolic acids were found to react with secondary amines in the presence of paraformaldehyde, at 140 °C in water to give the desired propargylamines in good yield.